Chikungunya virus infection in human microglial C20 cells induces mitochondria-mediated apoptosis - Kumar, Narendra; Santhoshkumar, Rashmi; Venkataswamy, Manjunatha M. (Frontiers in Cellular and Infection Microbiology, 2024)
Chikungunya virus (CHIKV) infection is associated with acute clinical manifestations and chronic joint inflammation. CHIKV infection has gained much significance as a causative agent of central nervous system (CNS) complications, including encephalitis and related sequelae. Microglial cells, play a crucial role in immune responses and tissue repair in the CNS, with their activation potentially leading to either protection or pathology.In this study, we investigated the infection biology of CHIKV in the recently immortalized C20 human microglial cell line. The C20 cells were found to be permissible to CHIKV infection, similar to Vero cells, as the virus could replicate well in C20 cells and cause cytopathic effects. CHIKV-infected C20 cells showed a higher loss of cell viability compared to Vero E6 cells. Ultrastructural analysis revealed viral replication, formation of mature virions, distinct cytoplasmic and nuclear changes in infected cells with elongated mitochondria and cytopathic vacuoles. CHIKV infection induced apoptosis in C20 cells, with a significant decrease in cell viability. Further, CHIKV infection caused depolarization of mitochondrial membrane potential and altered the expression of cell surface markers such as CD11c, CD14, and HLA-DR. A marked decrease in CD14 expression was noted with increased apoptosis in CHIKV-infected C20 cells. The study findings suggest that CHIKV infection induces apoptosis in C20 microglial cell line through the mitochondrial pathway with significant alteration in cell surface markers such as CD14 that is linked with induction of apoptosis.